PENGARUH PENGAWASAN KERJA TERHADAP DISIPLIN KERJA KARYAWAN ( Kasus Karyawan PT. Lotte Shopping Indonesia Cabang Pekanbaru) - Manik, Ima Sarianti; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Oversight of the work of the employees should be of particular concern for companies because supervision is one way to ensure that employees are doing the job duties and discipline in accordance with existing labor standards. Supervision of work has a significant impact on employee discipline that will increase the effectiveness of the work.This study aimed to determine the effect of work on the discipline supervision of employees PT.Lotte Shopping Indonesia Branch Pekanbaru. Data obtained from the questionnaire with the number of respondents are 55 further processed using descriptive statistics and then the data is presented in tabular format with the numbers and percentages for subsequent analysis results indicate that supervision has a pretty good influence on the discipline of employees in PT.Lotte Shopping Indonesia Branch Pekanbaru. Labor discipline is influenced by supervisory work with R Square value of 0.295. What this means is that the contribution of labor control variable influence to variable labor discipline employees amounted to 29.5%, while the remaining 70.5% is influenced by other factors.Keywords: supervision of work, work discipline , effectiveness of the work.